A cross-sectional study of lung functions in traffic police personnel at work in Kathmandu Valley, Nepal - Shrestha, Hari Sunder; Nepal, Ojashwi; Khanal, Kishor; Kapoor, Bhoopinder Kumar (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
BACKGROUND: The present study was aimed to assess pulmonary functions in the traffic police personnel (TPP) posted on traffic duty in Kathmandu valley, Nepal. METHODS: The study group consisted of 17 females and 89 males, constituting 16% and 84% of the total police personnel studied, respectively. In the control group of 25 individuals, 16% (n=4) were female and 84% (n=21) were male. Portable desktop spirometer was used for the pulmonary function test (PFT) measurements. RESULTS: It is seen that in females as compared to males, PFT parameters show a significant decrease. One-way ANOVA conducted to compare the effect of duration of air pollution exposure showed that there is a significant variation in PFT parameters among the groups. The exposure duration has significant effect on the PFT parameters. CONCLUSION: Greater the officers are engaged in traffic duty for years, greater is the decrement in their lung functions test. DOI: http://dx.doi.org/10.3126/acclm.v1i1.12315 Ann. Clin. Chem. & Lab. Med. 1(1) 2015: 42-48